Cancer stem cells within moderately differentiated head and neck cutaneous squamous cell carcinoma express components of the renin-angiotensin system. Issue 9 (September 2019) - Nallaiah, Shanella; Lee, Valerie Ming Yi; Brasch, Helen D; de Jongh, Jennifer; Schaijik, Bede van; Marsh, Reginald; Tan, Swee T; Itinteang, Tinte
Summary: Purpose: To investigate the expression of components of the renin-angiotensin system (RAS): pro-renin receptor (PRR), angiotensin converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1) and angiotensin II receptor 2 (ATIIR2) by the cancer stem cell (CSC) subpopulations in moderately differentiated head and neck cutaneous squamous cell carcinoma (MDHNCSCC). Methodology: 3, 3-Diaminobenzidine (DAB) immunohistochemical (IHC) staining for PRR, ACE, ATIIR1 and ATIIR2 was performed on formalin-fixed paraffin-embedded sections of ten MDHNCSCC tissue samples. Immunofluorescence (IF) IHC staining was used to localise components of the RAS. Western blotting (WB) and RT-qPCR were performed on snap-frozen MDHNCSCC tissue samples and MDHNCSCC-derived primary cell lines to investigate protein transcription expression of these proteins, respectively. Results: DAB IHC staining demonstrated the presence of PRR, ACE, ATIIR1 and ATIIR2 in all ten MDHNCSCC tissue samples. IF IHC staining showed expression of PRR and ATIIR2 by the OCT4 + cells, and ACE and ATIIR1 by the SOX2 + cells, within the tumour nests (TNs) and the peritumoural stroma (PTS). PRR, ACE, ATIIR1 and ATIIR2 were expressed by the endothelium of the microvessels within the PTS. WB confirmed protein expression for PRR, ACE and ATIIR1 in MDHNCSCC tissue samples and MDHNCSCC-derived primary cell lines. RT-qPCR showed transcriptional activation of PRR, ACE, ATIIR1 and ATIIR2 in MDHNCSCC tissue samples; and PRR, ACE, ATIIR1 but not ATIIR2, in MDHNCSCC-derived primary cell lines. Conclusion: PRR, ACE, ATIIR1 and ATIIR2 are expressed by the CSC subpopulations within the TNs, the PTS, and the endothelium of the microvessels within the PTS, in MDHNCSCC.